(untitled) (European Journal of Pure and Applied Mathematics, 2010)
We provide an algorithm to find a minimal set of generators for the Rees algebra associated toÂ rational space curves of type (1,1,d-2) in projective 3-space based solelyÂ on a μ-basis of the curve. We also illustrate the geometry behind the generators via a case study of rational quartic space curves.